Motor Learning Induces Profound but Delayed Dendritic Plasticity in M1 Layer II/III Pyramidal Neurons. (21st August 2020) - Streffing-Hellhake, P.; Luft, A.R.; Hosp, J.A.
Highlights: Motor learning induces a decrease in dendritic length of layer II/III M1 neurons. Parallel increment in spine density is likely a consequence of ageing. Spine morphology changes indicate prior synaptic plasticity. Changes evolve over two months after training ended. Learning induced plasticity in M1 layer II/III neurons has a delayed dynamic. Abstract: Motor learning depends on plastic reorganization of neural networks within the primary motor cortex (M1). In the circuitry of M1, integration and processing of afferent inputs is executed by pyramidal neurons of layer II/III. Thus, an involvement of these layer II/III pyramids in learning-induced changes is highly plausible. We therefore analyzed dendritic plasticity in layer II/III pyramidal cells on Golgi-Cox silver-impregnated sections after training of a forelimb reaching task. Based on their location within layer II/III, neurons were assigned to either a superficial or a deep population. After training, morphological changes occurred in both superficial and deep layer II/III pyramids. Overall, a decrease in dendritic length could be observed. In detail, superficial cells showed a significant reduction in the length of the apical dendrite after training ended in contrast to deep layer II/III pyramids, where dendritic length initially remained stable. Both types of neurons showed a transient increment in complexity of the distal apical dendrite 30 days after training. Findings were different in basal dendrites: length and complexity continuously decreased in superficial and deep layer II/III pyramids. Spine density increased in apical and basal dendrites of both superficial and deep layer II/III neurons, likely an effect of ageing that occurred independently from motor learning. This increase in spine density was accompanied with a morphological change towards stubby- and mushroom-like spines. Thus, profound but delayed changes occurred within the dendritic compartment of layer II/III pyramidal cells.